2021
DOI: 10.3390/cells10020236
|View full text |Cite
|
Sign up to set email alerts
|

Non-Thermal Biocompatible Plasma Jet Induction of Apoptosis in Brain Cancer Cells

Abstract: Glioblastoma multiforme (GBM) is a highly malignant and rapidly advancing astrocytic brain tumor in adults. Current therapy possibilities are chemotherapy, surgical resection, and radiation. The complexity of drug release through the blood-brain barrier, tumor reaction to chemotherapy, and the inherent resistance of tumor cells present challenges. New therapies are needed for individual use or combination with conventional methods for more effective treatment and improved survival for patients. GBM is difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Akter and colleagues have also observed an increase in the G1 to G2 ratio of the cell cycle following gas plasma-exposed glioblastoma cells [36], as observed in our study. The authors also found GBM cells to be more sensitive to gas plasma exposure than non-malignant astrocytes [61]. Albeit our comparison cell line HaCaT derives from the skin and is less suitable as the control, its greater sensitivity to the gas plasma treatment is in line with previous findings that some tumor cell types are more sensitive to this non-malignant cell type while others are less sensitive [62], exemplifying that such comparisons are often relative.…”
Section: Discussionsupporting
confidence: 88%
“…Akter and colleagues have also observed an increase in the G1 to G2 ratio of the cell cycle following gas plasma-exposed glioblastoma cells [36], as observed in our study. The authors also found GBM cells to be more sensitive to gas plasma exposure than non-malignant astrocytes [61]. Albeit our comparison cell line HaCaT derives from the skin and is less suitable as the control, its greater sensitivity to the gas plasma treatment is in line with previous findings that some tumor cell types are more sensitive to this non-malignant cell type while others are less sensitive [62], exemplifying that such comparisons are often relative.…”
Section: Discussionsupporting
confidence: 88%
“…NBP has been reported to have a selective killing effect on targeted cancer cells with minimal effects on regular cells that act by generating reactive oxygen species (ROS) and reactive nitrogen species (RNS). In previous study, we assessed the effects of a non-thermal air soft jet plasma on the U87 brain cancer by using the physicochemical and biological (PCB) correlation between the RONS cascade and MAPK/PI3K/AKT signaling pathway, which resulted in apoptosis [175,176]. The results showed that the soft jet plasma significantly inhibited cell proliferation, induced cell cycle arrest, inhibited survival pathway and induced apoptosis pathway in U87 cells (Fig.…”
Section: Cellular Mechanism Of Nbp As Plasma Treated Liquid For Cancermentioning
confidence: 99%
“…Recently, nonthermal biocompatible atmospheric-pressure plasma (i.e., cold plasma) has provided a new horizon for various prospective biomedical applications [ 137 , 138 , 139 , 140 , 141 , 142 ], and represents a promising technique for the treatment of cancers and tumors without harming normal cells or tissues. Over the past few decades, “plasma medicine” has been used for its anticancer properties [ 143 , 144 , 145 , 146 , 147 , 148 ], including one clinical study [ 149 ].…”
Section: Biological Effects Of Microwavesmentioning
confidence: 99%
“…Nonthermal plasma has a wide range of applications in modern age in several areas [ 11 , 151 , 152 , 153 ]. It comprises multiple energies in the form of electrons, ions, and reactive oxygen and nitrogen species (RONS) [ 154 , 155 , 156 , 157 ], for which cocktails of the latter have been shown to have apoptotic properties in cancer cells [ 140 , 158 ]. As cancer cells maintain different mechanisms to normal cells, it has been reported that ROS uptake by cancer cells induces apoptosis via intrinsic or extrinsic pathways in brain tumors.…”
Section: Biological Effects Of Microwavesmentioning
confidence: 99%